MIGA Annual Report 2017 : Insuring Investments, Ensuring Opportunities - Multilateral Investment Guarantee Agency (Washington, DC, 2017)
In fiscal year 2017, MIGA continued to work on the WBG’s twin goals of eradicating extreme poverty and promoting shared prosperity by focusing on IDA (low income) countries, Fragile and Conflicted States, Climate Change and Innovation. Projects we supported will help 8.5 million people gain access to power, help avoid 1.1 million tons of greenhouse gas emissions, and enable access to healthcare for 8.7 million patients. We issued $4.8 billion in guarantees to private investors. This is a record for MIGA. Nearly half of our projects were in IDA. We also continued to work tirelessly to ensure that we supported investments in fragile and conflict-affected countries, which make up 10% of our portfolio.